Odpowiedź :
a)2⁻³ = ½³ =1/8
b) (½)⁻²= 2² =4
c) (-3)⁻² = (-⅓)² = 1/9
d) (-1)⁻¹=(-1)
e) (2⅓)⁻¹= (7/3)⁻¹ = (3/7)¹ =3/7
f) (-1)⁻⁴= (-1)⁴ =1
g) (1¾)⁻¹ = (7/4)⁻¹ =(4/7)¹ = 4/7
h) (0,2)⁻¹ = (2/10)⁻¹= (10/2)¹= 10/2= 5
b) (½)⁻²= 2² =4
c) (-3)⁻² = (-⅓)² = 1/9
d) (-1)⁻¹=(-1)
e) (2⅓)⁻¹= (7/3)⁻¹ = (3/7)¹ =3/7
f) (-1)⁻⁴= (-1)⁴ =1
g) (1¾)⁻¹ = (7/4)⁻¹ =(4/7)¹ = 4/7
h) (0,2)⁻¹ = (2/10)⁻¹= (10/2)¹= 10/2= 5
a)2⁻³ = 1:2³=⅛
b)½⁻² = 1:½² = 1:¼ = 4
c)-3⁻² = 1:3²= 1:9
d)-1⁻¹ = 1:-1¹ = 1:-1
e)11:5⁻¹=1:(11:5) = 5:11
f)-1⁻⁴= 1:1⁴= 1
g)7:4⁻¹ = 1:(7:4) = 4:7
h)1:5⁻¹ = 1:(1:5) = 5
b)½⁻² = 1:½² = 1:¼ = 4
c)-3⁻² = 1:3²= 1:9
d)-1⁻¹ = 1:-1¹ = 1:-1
e)11:5⁻¹=1:(11:5) = 5:11
f)-1⁻⁴= 1:1⁴= 1
g)7:4⁻¹ = 1:(7:4) = 4:7
h)1:5⁻¹ = 1:(1:5) = 5